Cysteine Pathogenic Variants of PMM2 Are Sensitive to Environmental Stress with Loss of Structural Stability. (25th January 2023) - Yu, Fan; Lin, Li; Sun, Jingmiao; Pan, Jicheng; Liao, Yixin; Pan, Yunfan; Bai, Guannan; Ma, Liangjian; Mao, Jianhua; Hu, Lidan
Abstract : Congenital disorders of glycosylation (CDG) are severe metabolic disorders caused by an imbalance in the glycosylation pathway. Phosphomannomutase2 (PMM2-CDG), the most prevalent CDG, is mainly due to the disorder of PMM2. Pathogenic variants in cysteine have been found in various diseases, and cysteine residues have a potential as therapeutic targets. PMM2 harbor six cysteines; the variants Cys9Tyr (C9Y) and Cys241Ser (C241S) of PMM2 have been identified to associate with CDG, but the underlying molecular mechanisms remain uncharacterized. Here, we purified PMM2 wild type (WT), C9Y, and C241S to investigate their structural characteristics and biophysical properties by spectroscopic experiments under physiological temperature and environmental stress. Notably, the variants led to drastic changes in the protein properties and were prone to aggregate at physiological temperature. Meanwhile, PMM2 was sensitive to oxidative stress, and the cysteine pathogenic variants led to obvious aggregate formation and a higher cellular apoptosis ratio under oxidative stress. Molecular dynamic simulations indicated that the pathogenic variants changed the core domain of homomeric PMM2 and subunit binding free energy. Moreover, we tested the potential drug targeting PMM2-celastrol in cell level and explained the result by molecular docking simulation. In this study, we delineated the pathological mechanism of the cysteine substitution in PMM2, which addressed the vital role of cysteine in PMM2 and provided novel insights into prevention and treatment strategies for PMM2-CDG.